2014
DOI: 10.1523/jneurosci.4972-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Modify Exercise-Induced Development of Stem Cell-Derived Neurons in the Adult Brain

Abstract: Neural stem cells in the adult mammalian hippocampus continuously generate new functional neurons, which modify the hippocampal network and significantly contribute to cognitive processes and mood regulation. Here, we show that the development of new neurons from stem cells in adult mice is paralleled by extensive changes to mitochondrial mass, distribution, and shape. Moreover, exercise-a strong modifier of adult hippocampal neurogenesis-accelerates neuronal maturation and induces a profound increase in mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 69 publications
8
134
0
1
Order By: Relevance
“…Physical exercise has been shown to enhance adiponectin production by reducing fat mass and inflammation in obese/diabetic patients (12). Given the important role of AMPK in mitochondrial biogenesis (45), which is required for running-accelerated newborn neuron maturation (46), increase in hippocampal adiponectin after running may modulate mitochondria biogenesis via activation of AMPK in the newborn cells, thereby enhancing neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise has been shown to enhance adiponectin production by reducing fat mass and inflammation in obese/diabetic patients (12). Given the important role of AMPK in mitochondrial biogenesis (45), which is required for running-accelerated newborn neuron maturation (46), increase in hippocampal adiponectin after running may modulate mitochondria biogenesis via activation of AMPK in the newborn cells, thereby enhancing neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this holds true for mammalian NSPCs remains to be determined. Further evidence that there is an increase in oxidative phosphorylation with neuronal differentiation comes from a recent study by Steib and colleagues, who have shown that the development of new neurons in adult mice is paralleled by extensive changes in mitochondrial mass, distribution, and shape (Steib et al, 2014). When inhibiting a mitochondrial fission factor necessary for increasing the numbers of mitochondria, maturation and survival of newborn neurons was strongly decreased.…”
Section: Metabolic Influence On Nspc Behaviormentioning
confidence: 99%
“…Further, two Drp1 constitutive knockout mouse models displayed severe neurodevelopmental defects [25,26], and similar observations were made in a human infant born with a de novo dominant-negative Drp1 mutation [27] and in patients with mutations in the mitochondrial Drp1 receptor, Mff [28]. Moreover, deleting Drp1 in adult neuronal stem cells leads to defective differentiation [29,30]. The importance of Drp1 function for differentiating and proliferating tissues is also underlined by the decrease of tumor aggressiveness upon treatment with Drp1 inhibitors [31][32][33].…”
Section: Commentarymentioning
confidence: 63%